Development and optimization of vermitea vortex brewer - Abenoja, Ryan M. (Southeastern Philippines Journal of Research and Development, 2020)
Vermitea is a liquid mixture produced by aerated or non-aerated mixing of vermicast to water. The introduction of vortex brewers had made progress in producing vermitea in terms of faster brewing time. Commercial vortex brewer is expensive and is not locally available in the Philippines. This study aimed to develop and test a locally made vortex brewer. The effects of varying amounts of air flow rate (at T1 -7.2 L min-1, T2 -14.4 L min-1, T3 -21.6 L min-1, T4 - control/non-aerated) during the brewing process to the operating time, machine performance, and properties of produced vermitea were determined. The establishment of brewing time was conducted for 24 hours and the fastest time was identified for T3 and T4 at 12 hours while longer brewing time of 20 hours was identified for T1 and T2. It was observed that the brewing time was shorter for the brewer using highest air flow rate during brewing. The largest recovery was recorded by the brewer with the lowest flow rate (T1) which was 93.39%. The brewing efficiency of the fabricated brewers was above the critical value. Also, the produced vermitea by all brewers has no foul odor which was an indication of proper aeration. The pH levels of the produced vermitea are all acidic, at a range of 6.19 to 6.86, but are still within the acceptable range. An economic analysis indicates that the most economically feasible was brewer T2 with 7.2 min-1 air flow rate.